A study of angiographic severity in patients with coronary artery disease and hyperuricemia - Pramanik, Subhraprakash; Mondal, Koushik; Dey, Arpan Kumar; Mandal, Pijush Kanti; Das, Shovan Kumar; Momin, Tanmoy W; Mitra, Mrinmoy; Mondal, Monojit; Dutta, Satyendra Nath (Asian Journal of Medical Sciences, 2015)
Backgrounds: Hyperuricemia has not yet been established as cardiovascular risk factor. We aimed to study the angiographic severity in patients with coronary artery disease (CAD) and hyperuricemia. Materials and Methods: In this observational cross-sectional study we measured serum uric acid level in 82 patients of CAD who underwent coronary angiography in catheterisation laboratory of our Institution. Severity of CAD was determined on the basis of Gensini score, number of diseased vessels, critical lesions and total occlusions. Results: The prevalence of hyperuricemia in patients with CAD was 42.68% in our study. Hyperuricemia was associated with higher Gensini score (33.33±10.64 vs. 22.90±6.75, p value <0.001), number of critical lesions (1.03±0.84 vs. 0.63±0.72, p value 0.031), total occlusions (0.67±0.47 vs. 0.37±0.48, p value 0.007) and dyslipidemia (63.6% vs. 30.6%, p value 0.003) more frequently compared to normouricemic patients. And also the higher serum uric acid level was correlated with higher Gensini score (beta 0.418, t 4.430, p value <0.001, 95% CI 0.036 and 0.094) and frequent number of total occlusion (beta 0.338, t 3.589, p value 0.001, 95% CI 0.462 and 1.613). Conclusion: Hyperuricemia was associated with higher Gensini score, frequent total occlusions and critical lesions in patients with Coronary Artery Disease compared to patients with normal uric acid level and also it was significantly correlated with higher Gensini score and frequent total occlusions. Asian Journal of Medical Sciences Vol.7(2) 2015 1-4